Security Challenges to provide Intelligence in SDN with the help of Machine Learning or Deep Learning - Shailesh Pramod Bendale, Jayashree Rajesh Prasad (International Journal of Advanced Science and Technology, 2020)
Since the 5G is the new upcoming technology, every stakeholder is not interested in investing on new CAPEX (capital expenditure) and OPEX (operational expenditure) resources. They all need a solution which will use the existing resources or will not require every time to purchase new resources. Due to this reason SDN came into the existence, to provide the required resources through SDN as and when required without increasing the CAPEX and OPEX. But as the solutions are switching to SDN it provides many features like centralized control, separation of control and data planes, programmability of the network, functionalities like Firewall, Load balancers, IDS, IPS as virtual functionalities on top of the controller. But current scenario of 5G will require more robust and fast security mechanisms as compared with earlier solutions. So there is a need of machine learning or deep learning to be introduced in the area of SDN for providing the security. We will discuss various security challenges which require the immediate attention and discuss some of the solutions for it.